Bioconversion of food waste to biocompatible wet-laid fungal films - Maximilian Benedikt Maria Köhnlein; Tiffany Abitbol; Ana Osório Oliveira; Mikael S. Magnusson; Karin H. Adolfsson; Sofie E. Svensson; Jorge A. Ferreira; Minna Hakkarainen; Akram Zamani (Materials & Design, 2022)
The fungus Rhizopus delemar was grown on bread waste in a submerged cultivation process and wet-laid into films. Alkali or enzyme treatments were used to isolate the fungal cell wall. A heat treatment was also applied to deactivate biological activity of the fungus. Homogenization of fungal biomass was done by an iterative ultrafine grinding process. Finally, the biomass was cast into films by a wet-laid process. Ultrafine grinding resulted in densification of the films. Fungal films showed tensile strengths of up to 18.1 MPa, a Young’s modulus of 2.3 GPa and a strain at break of 1.4%. Highest tensile strength was achieved using alkali treatment, with SEM analysis showing a dense and highly organized structure. In contrast, less organized structures were obtained using enzymatic or heat treatments. A cell viability assay and fluorescent staining confirmed the biocompatibility of the films. A promising route for food waste valorization to sustainable fungal wet-laid films was established.